Institutional Reconstruction of The Indonesian Ulama Council Within The Indonesian Government System - Yudi Widagdo Harimurti; Safitri Safitri; Ansori Asnori (UNISKA LAW REVIEW, 2023)
The Indonesian Ulama Council (MUI) is an institution that houses Muslim scholars and intellectuals throughout Indonesia. Whether it is requested or not, one of the functions of The Indonesian Ulama Council is to give a legal opinion (fatwa) towards Muslims and the government. MUI fatwas provide a significant role for society and the government, it is proven by the use of the MUI fatwa as a guideline for the community in responding to daily problems related to religion. Many fatwa materials are implemented in several laws and regulations including sharia issues, narcotics, banking, waqf, pornography, and others. However, MUI Fatwas do not have the binding force of law because of its MUI position as a social organization, not a state institution. Therefore, this research was conducted to explain further the existence of MUI in the constitutional system of the Republic of Indonesia and how MUI should be arranged in the constitutional system of the Republic of Indonesia. This research employed a normative research method. The approach used was the statute approach and the historical approach. The results of this study indicate that MUI has an important role in the constitutional system of the Republic of Indonesia. It is proven by the issuance MUI fatwa stated that MUI Fatwa becomes part of the legal basis for the state and becomes a referral source for the government in making decisions. Thus, a better arrangement of MUI in the constitutional system of the Republic of Indonesia must be carried out to maintain the legal force of the MUI Fatwa involvement in the constitutional system of the Republic of Indonesia.